Population size estimation of female sex workers using network scale-up method in Kermanshah city - Lida Olfati; Roya Safari-Faramani; Farid Najafi; Mehdi Moradi Nazar; Ebrahim Shakiba (BMC, 2023)
Abstract Background Appropriate estimate of size of the female sex workers as well as the other hard-to-reach-populations plays a crucial role in reaching them with effective preventive measures. This study aimed to estimate the population size of female sex workers in Kermanshah City using the network scale-up method. Method In this cross-sectional study, of the 1000 pedestrians aged between 18 and 65 years, selected from the population of Kermanshah City via a multistage sampling, were recruited in the study. Face-to-face interview using a questionnaire including the number of FSWs in the social network of the respondent was used to collect the data. Results The overall estimated number of female sex workers in the general population was 4848(UI 95%: 4597, 5074). Accordingly, the prevalence of FSWs among women 18 years and older in Kermanshah in 2018 was about 11.92 (UI 95%: 11.30, 12.47) in one thousand. More than half of the female sex workers in the respondent's social network were unmarried and were in the age range of 18 to 29, and had a high school or university degree. Among high-risk behaviors, a history of alcohol consumption accounted for the highest percentage. Conclusion The number of female sex workers estimated in this study is considerable, which highlights the importance of planning harm reduction interventions in order to alleviate the burden of HIV infection in the population.